BANK SELECTION FACTORS IN THE BANKING INDUSTRY: AN EMPIRICAL INVESTIGATION FROM POTENTIAL CUSTOMERS IN NORTHERN CYPRUS - Katircioglu, S. T.; Fethi, S.; Unlucan, D.; Dalci, I. (Akademiai Kiado Rt, 2011)
This study investigates the bank selection criteria of undergraduate students who are future potential customers of banks from different regions of the world in a small island economy by comparing the selection factors of international students for the first time. Survey results of 258 respondents show that there are not huge differences in the bank selection factors between Turkish and non-Turkish international students in the case of a state university in North Cyprus. Availability and convenient location of ATM services and speed and quality of service are the most important factors for considering banks and their services for both Turkish and non-Turkish undergraduate students.
Keywords: bank selection factors; undergraduate students; university